Higher Order Thinking Laboratory (HOT Lab)-Based Physics Learning: A Systematic Literature Review - Mujib Ubaidillah; Putut Marwoto; Wiyanto Wiyanto; Bambang Subali (Universitas Negeri Semarang, 2022)
This study aims to analyze physics learning based on HOT Laboratory. The research method uses a literature review. Data collection was based on the Scopus, DOAJ, IOP Science, and Google Scholar database sources. The types of documents come from journal articles and conference papers with the keywords